Design, Simulation and Fabrication of a Novel Phage Filter for Pathogens Testing from Large Volumes of Water. (25th October 2017) - Lu, Xu; Du, Songtao; Horikawa, Shin; Chen, I-Hsuan; Liu, Yuzhe; Chin, Bryan A.
Abstract : In this paper, a phage filter has been developed to capture, concentrate and isolate small numbers of pathogens from large volumes of water. The phage filter consists of a magnetized filter frame and hundreds of phage-coated filter elements made of a magnetoelastic material. ANSYS Maxwell simulations have been conducted on filter designs. Pairs of magnets were used to generate a uniform magnitude of magnetic flux density and a desired direction of flux vectors to align and hold filter elements on the frame. The strip-like filter elements were made of Metglas 2826MB ribbon by mechanically dicing. A prototype filter with high density of filter elements in the size of 2″ has been demonstrated.